A sociocultural study of identity formation among novice EFL teachers in Vietnamese higher education - Nguyen, Huong Tra; Le, Thanh Thao (Frontiers in Education, 2025)
IntroductionThis study examines how three novice English as a foreign language (EFL) lecturers in Vietnamese higher education construct their professional identities during the probationary period.MethodsFramed by social constructivism and situated learning, we analyze semi-structured interviews using reflexive thematic analysis. We address a persistent gap in recent EFL identity research: limited attention to probationary novices in Southeast Asia, where globalized pedagogies intersect with Confucian-influenced institutional cultures.ResultsFindings show identity as negotiated across four interlocking trajectories: becoming an authoritative-yet-relational instructor, acting as a cultural mediator between global and local pedagogies, learning through mentorship and collegial participation, and cultivating situated resilience.DiscussionWe argue that identity work emerges from participation in departmental communities and classroom routines rather than from method adoption alone. Implications include structured, dialogic mentoring, culturally responsive pedagogy adaptation, and reflective checkpoints during probation. The study contributes an empirically grounded account of identity-in-practice in a rapidly reforming system and speaks to international debates on early-career teacher support in EFL higher education.